Material legacy of Stanisław Polakowski, a teacher from the turn of the 19th and 20th centuries - Złotkowski, Dariusz (In the Mirror of Things, 2022)
In 1995, my book entitled Życie zawodowe i rodzinne Stanisława Polakowskiego 1880–1943 nauczyciela szkół wiejskich w świetle jego notatek i korespondencji (Professional and Family Life of Stanisław Polakowski, 1880–1943, a Rural School Teacher in the Light of His Notes and Correspondence) was published. One usually reconstructs the life path and professional achievements of a given person on the basis of written sources. This article attempts to show how precious preserved material legacy can be. In case of the aforesaid teacher, the „treasure” consisted of notebooks and textbooks from his school years, a violin brought from Veiveriai, and press and books from the turn of the 19th and 20th centuries in Russian and Polish. Notes made on the margins of small calendars or notepads concerning his family, the weather or war events of 1914 turned out to be very useful, too. Gradually, other objects were added to the list: a camera, a radio set, a Singer sewing machine. Those artifacts have survived in a family house of the Polakowski family in Poraj, built during his retirement. Over the years, the family was aware that their father’s personal belongings were as precious as written sources. It is worth the mention that in 2007 the inhabitants of Strzyżowice and its education authorities decided to choose Stanisław Polakowski as the patron of the local primary school.